La doctrina jurisprudencial del tribunal constitucional sobre despido y su influencia en la protección legal contra el despido arbitrario - Laiza Espinoza, Gloria Lucila (2011)
This thesis contains research and analysis of the influence of the jurisprudence of the Constitutional Court in its constitutional rulings contained in the system of legal protection against arbitrary dismissal in our labor law, enshrined in Article 34 of the Act Labor productivity and competitiveness, consolidated text which was approved by Supreme Decree No. 003-97-TR. In this context, the framework of our research is structured on the basis of study and research of the jurisprudence of the Constitutional Court and its influence on the protection against arbitrary dismissal, where he performed, in principle, a study of legitimacy, function and purpose of the Constitutional Court as comptroller of the Constitution also emphasizes the study of legal stability provided for in Article 34 of Law Labor productivity and competitiveness and the impact of the constitutional jurisprudence of the Constitutional Court, jurisprudential constructions called "groundless dismissal and dismissal fraudulent." This work contains the basis of the Constitutional Court case law and is considered its most emblematic judgments as judgments in the cases 1124-2001-AA/TC number, if followed by the Trade Union of workers of Telefonica del Peru and FETRATEL against Telefonica del Peru and 976-2001-AA/TC, if followed by Eusebio Llanos Huasco against Telefonica del Peru, carrying out a study of the relationship with each of the cases cited and a panoramic approach to the interpretation of Article 27 of the Constitution , which mandates the development of legal protection against arbitrary dismissal. Addressed in strict jurisprudential assumptions identified in the constitutional rulings of the Constitutional Court in its jurisprudence, as regards dismissal and the dismissal uncaused fraudulent, statements issued during the period 2000-2008. Finally we arrive at the conclusion of this thesis, that the jurisprudence of the Constitutional Court regarding the protection of the right to work, meant to give the work order to protect an area which is located in plane higher than the regulated and the scope of legal protection against arbitrary dismissal set out in Article 34 of Law of productivity and competitiveness, relative job security, because protection is granted to make restitution to find a violation of a constitutional right as the right to work on his second essential "but not being fired for just cause"